Mutational analysis of the Janus kinase II (V617F) gene in patients with β-Thalassemia major - Salar A. Ahmed (Zanco Journal of Pure and Applied Sciences, 2020)
β-Thalassemia is a group of congenital hemolytic anemia that characterized by the underproduction of the indispensable hemoglobin molecule, the oxygen and carbon dioxide carrying protein inside the red cells. With our current study, we’ve screened if some extent mutation at Valine 617 Phenylalanine of Janus kinase II genes detectable in β-thalassemia major in our region. The present study for the screening of JAK II V617F mutation was conducted on (50) patients with β-thalassemia major, restriction fragment length polymorphism with restriction endonuclease enzyme AflIII was used to identify a flaking region of 617 for JAK II gene. In the existing study, no mutation has been detected within the patients suffering from β-thalassemia major. Our results indicate that JAK II V617F mutation appears to not be associated with thromboembolic complications related to β-Thalassemia and therefore the incidence of β-Thalassemia. To the best of our knowledge, this study is the first evidence to determine the status of JAK II V617F mutation in patients with Thalassemia major in our region and expands the international published literature on it.